Exploring the Role of Mindfulness Meditation in Facilitating English Learning and Optimizing Classroom Teaching - Zhao, Xin (Journal of Psychology and Behavior Studies, 2024)
Mindfulness meditation is a technique for regulating attention and emotions, which can help individuals enhance self-awareness and reduce stress. This paper aims at review the positive effects of mindfulness meditation on English learners and teachers, including improving English learning abilities and enhancing motivation, confidence, and enjoyment in English learning. Through systematic literature searches and screening methods from databases such as CNKI, Wan fang, Pub Med, and Web of Science, relevant papers on mindfulness meditation and English learning from the past decade were selected. Their research purposes, methods, innovations, and conclusions were analyzed. This paper specifically explores the literature review on the impact of mindfulness meditation on English learning, summarizing both the theory and practice of mindfulness meditation, and proposing future research directions and suggestions. Mindfulness meditation has a positive impact on English learning and classroom teaching, but its specific effects are influenced by various factors such as the type, duration, and frequency of mindfulness meditation. More empirical research is needed to validate its effects on English learning and to explore the optimal integration methods.